Accumulation of biomass, physiological characteristics and grain yield of bean cultivars under irrigated and dry regimes - Gomes, Arão Araújo; Araújo, Adelson Paulo; Rossiello, Roberto Oscar Pereyra; Pimentel, Carlos (Pesquisa Agropecuaria Brasileira, 2000)
In a field experiment, the vegetative growth and the grain yield of four common bean (Phaseolus vulgaris L.) cultivars were evaluated under irrigated or rainfed conditions, corresponding to total water levels of 252 and 123 mm, respectively. Leaf area and shoot biomass were weekly measured. The water stress reduced the shoot biomass, the leaf area index and the crop growth rate of all cultivars. There was no significant difference between cultivars in grain yield under rainfed; however, the water stress reduced grain yield in cultivars, except for Negro Argel. The number of pods per plant was the yield component most affected by the irrigation regimes. Under rainfed, ’Negro Argel’ presented lower reductions in stem biomass at the end of growth cycle, in leaf area duration, and in grain yield, demonstrating a higher drought tolerance, whereas Carioca was the cultivar most sensitive to water stress.